Pengaruh Kepuasan Kerja dan Stres Kerja Terhadap Turnover Intention Karyawan : (Studi Kasus Pada PT. AAE Outdoor Indonesia, Kecamatan Bulakamba, Kabupaten Brebes, Jawa Tengah) - Muhamad Reza Nurhakiki; Nur Afridah; Dwi Harini (Universitas 45 Surabaya, 2024)
This research aims to determine the effect of job satisfaction and work stress on employee turnover intention at PT. AAE Outdoor Indonesia. Meanwhile, the formulation of the problem is how job satisfaction and job stress can influence turnover intention among PT employees. AAE Outdoor Indonesia. The population in this study was 772 while the sample was 92 taken from the sampling technique using the Slovin formula with a margin of error of 10%, while the results were that the job satisfaction variable (X1) had a significant and positive effect on PT turnover intention. AAE Outdoor Indonesia. It is proven that the tcount value is 6,141 > ttable value 1.986 and the resulting significant value of 0.000 is much smaller than α = 0.05, so Ho is rejected and H1 is accepted, meaning that the independent variable employee satisfaction (X1) partially has a significant effect on turnover intention (Y) PT AAE Outdoor Indonesia, the work stress variable (X2) has a significant and positive effect on turnover intention at PT. AAE Outdoor Indonesia. It is proven that the significant value is 00.000 < 0.05 and the tcount value is 6.278 > ttable 1.986, so Ho is rejected and H1 is accepted, meaning that the independent variable work stress (X2) partially has a significant effect on PT AAE Outdoor Indonesia's turnover intention (Y), satisfaction variable. work (X1) and work stress (X2) simultaneously have a significant and positive effect on turnover intention (Y). This is proven by the F test analysis which shows a significance of 0.000 < 0.05. Meanwhile, Ftable is (3.009), so Fcount is 78,890 > Ftable 3.009, so Ho is rejected, and Ha is accepted, likewise with a significance of (0.000) < α (0.05), then Ho rejected and Ha can be accepted. This means that the variables job satisfaction (X1) and work stress (X2) together have an influence on turnover intention (Y) at PT. AAE Outdoor Indonesia.